Local supervisor model for distributed reconfiguration - DeBrunner, L.S.; Gray, F.G. ([1991] Conference Record of the Twenty-Fifth Asilomar Conference on Signals, Systems & Computers, 1991)
The local supervisor model (LSM) is presented as a basis for comparing and designing distributed reconfiguration algorithms. Cells designated as local supervisors work together in parallel to change the global structure through a series of separate actions requiring only short communication paths between close neighbors. The LSM was used to design the Array Reconfiguration Algorithm (ARA) and to compare two reconfiguration algorithms for a given architecture. ARA has been proven to reconfigure correctly for single faults in an N*M array embedded in an unbounded redundant graph.< >